Primary breast angiosarcoma resembling a common benign tumor: A case report. (May 2021) - Alshaar, Muhammad; Alkhatib, Mahmoud; Sara, Samer; Alsabek, Mhd Belal
Abstract: Introduction and importance: The breast angiosarcoma is a rare malignant vascular neoplasm; it represents nearly 0.05% of all breast cancers. Clinically, it could look like a haemangioma or pseudoangiomatous hyperplasia. Here, we report a case of a primary angiosarcoma of the breast (PAB) that mimics a giant fibroadenoma in physical examination and ultrasound features. Case presentation: A 22 year-old woman came to our hospital complaining of a mobile non-tender mass in her right breast. It was monitored for a while until it became an 8 × 7 cm 2 . Past medical and family histories were unremarkable. Ultrasonography showed a well circumscribed hypoechoic lobular mass. The wide excision was performed and the pathological study showed angiosarcoma. The patient was re-operated for total mastectomy, screened for distant Metastases and followed-up closely for one year. Clinical discussion: Fibroadenoma-like lesions are not uncommon and physicians should pay an attention for any breast mass even in the patient who is young and has no risk factors of the traditional breast cancer. PAB is used to be missed in the clinical practice over the world; it is extremely rare and is proved by Immunohistochemistry. The full management could be totally completed by a mastectomy with/out axillary node dissection. Conclusion: The primary angisarcoma of the breast (PAB) could resemble a fibroadenoma in pre-operative investigations. In many reviews, PAB mimicked many diseases. Thus, the medical literature needs more case reports and series to identify an ideal protocol of diagnosis and management. Highlights: Breast angiosarcoma still causes a diagnostic problem in young women. Clinically presentation and ultrasound features could mimic fibroadenoma. Pathological findings and immunohistochemistry make the definitive diagnosis. Young women shouldn't ignore the following-up of any breast lump.